RIEPT Trials - Ecosystems M: Poorly drained savannas - International Center for Tropical Agriculture (2015)
In 1978, CIAT"s Tropical Pastures Program, with the cooperation of national research institutions active in pastures research, took the initiative of forming the RIEPT (Red Internacional de Evaluación de Pastos Tropicales - i.e . lnternational Tropical Pastures Evaluation Network). Its central objectives were defined as, To contribute to the search for new pasture germplasm for the different production ecosystems prevalent in the poor, acid soils of the vast agricultural frontiers of the continent, Developing extrapolations based on knowledge of the range of ecosystems and subecosystems to which germplasm can adapt, Developing and promoting scientific capabilities within the network in order to achieve efficiency in the experimentation process, which, in a dynamic and sequential manner, will incorporate promising germplasm in pastures and put these in appropriate production systems.(Toledo, 1982)To fulfill these objectives, RIEPT was relied on Regional Trials A (RTAs) representing major ecosystems (well-drained isohyperthennic and isothennic savannas, poorly drained savannas, and rainy and semievergreen seasonal tropical forests), and carried out Regional Trials B (RTBs) at sites representative of the subecosystems found within these five major ecosystems. In the RTAs, an evaluation of the adaptation potential of germplasm under the conditions of a major ecosystem was first made, that is, the potential survival of the germplasm is assessed. The materials that survive and also show a high degree of productivity were exposed to subecosystem conditions in the RTBs, where evaluations were conducted under cutting to measure seasonal productivity (that is, under maximum and minimum rainfall), and so obtain a measurement that integrates adaptability and productivity potential. Until this stage, evaluations were made monoculture, in small plots, with the only purpose of selecting germplasm adapted to the natural conditions (soil, climate, biotic pressures) of different ecosystems. By using uniform evaluation methodologies, it was possible to make multilocational analyses that could extrapolate from known adaptation ranges of the selected germplasm.However, that agronomic experimentation (RTAs and RTBs) was not in any way sufficient to comply with the final objective of incorporating new germplasm options in pastures for animal production systems at the continent"s agricultural frontiers. RIEPT therefore proposed to carry out regional trials under grazing in two phases. In the first, known as Regional Trials C (RTCs), the idea was to incorporate new germplasm in pastures to study its potential compatibility under grazing in small plots in terms of productivity (dry-matter yields and carrying capacity) and persistence (dynamics of botanical composition, changes in plant architecture, and seed reserves) under different grazing management systems. In the second phase, Regional Trials D (RTDs), the best pastures in terms of productivity, persistence, and ease of management were compared with the best pastures under traditional use. In these trials, pasture productivity as animal products (beef, milk, and calves) within the context of the predominant production system in each region were measured.This dataset provides RIEPT trial data for activities conducted in poorly drained savannas.